Analisis Manfaat yang Diperoleh Masyarakat dalam Perspektif Gender pada Pengelolaan Agroforestry (Studi kasus: kawasan reboisasi Program JIFPro di Kabupaten Solok, Sumatera Barat) - Mutiara, Vonny Indah; Febriamansyah, Rudi; Fahmi, Innike Abdillah (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
This research was conducted in Jorong Subarang, Kanagarian Paninggahan, Junjung Sirih Suburb, Solok, West Sumatera where JIFRO program has been implemented in that area. The research aims to (1) analyze men and women contribution in terms of productive, reproductive and social activity; (2) analyze gender perception on benefit and cost of managing agroforestry in JIFPro program. A case study method is used in this research. The result shows that men are rarely involved in reproductive activities. Men manage most of their productive activities. On the other hand, women are not only spending more time on reproductive activities but also involved in productive activities. In addition, men and women equally spend their time on social activities.